2015
DOI: 10.1371/journal.pone.0117819
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome Analysis of Arabidopsis GCR1 Mutant Reveals Its Roles in Stress, Hormones, Secondary Metabolism and Phosphate Starvation

Abstract: The controversy over the existence or the need for G-protein coupled receptors (GPCRs) in plant G-protein signalling has overshadowed a more fundamental quest for the role of AtGCR1, the most studied and often considered the best candidate for GPCR in plants. Our whole transcriptome microarray analysis of the GCR1-knock-out mutant (gcr1-5) in Arabidopsis thaliana revealed 350 differentially expressed genes spanning all chromosomes. Many of them were hitherto unknown in the context of GCR1 or G-protein signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 60 publications
5
46
0
1
Order By: Relevance
“…It was found that gpa1-5 is similar to other known GPA1 mutants (Chen et al 2004 ;Jones et al 2003 ) with longer roots, fewer lateral roots, rounded leaves, reduced plant height, longer but fewer siliques, and smaller rosette ( Supplementary Fig. S1) as compared to the wild type, Ws2 (Chakraborty et al 2015 ). showing.…”
Section: Gpa1 Mutant Characterizationsupporting
confidence: 56%
See 2 more Smart Citations
“…It was found that gpa1-5 is similar to other known GPA1 mutants (Chen et al 2004 ;Jones et al 2003 ) with longer roots, fewer lateral roots, rounded leaves, reduced plant height, longer but fewer siliques, and smaller rosette ( Supplementary Fig. S1) as compared to the wild type, Ws2 (Chakraborty et al 2015 ). showing.…”
Section: Gpa1 Mutant Characterizationsupporting
confidence: 56%
“…In addition, genome-wide interactome analysis of various G-protein subunits has been reported in Arabidopsis (Klopffleisch et al 2011 ). Functional genomics and in silico studies have also begun to answer the doubts regarding the role of GCR1 in plant heterotrimeric G-protein signalling (Chakraborty et al 2015 ;Taddese et al 2014 ). However, we neither know the complete GPA1mediated signaling pathway for the regulation of a single gene/process, nor the total number of genes/processes regulated by GPA1 on an organism-wide scale, let alone those shared by GCR1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the complexity of these adversity‐response mechanisms, however, many minor changes in expression and signaling confer distinct response phenotypes, such as different levels of low‐Pi sensitivity in maize inbred lines. Therefore, the number of related metabolites showing large‐amplitude differences between genotypes is relatively limited, unlike the dramatic variations between mutants and wild types (Chakraborty et al ., ; Pant et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, las proteínas MLO presentan un dominio 7TM, pero no se ha podido confirmar su acoplamiento con proteínas G (Urano y Jones, 2013). En apoyo a la hipótesis de que GCR1 es un GPCR en plantas, Chakraborty et al (2015b) realizaron un análisis del transcriptoma bajo las mismas condiciones para GPA1 y GCR1 en el cual compararon los genes de respuesta identificados para GPA1 y GCR1, en el que encontraron 104 genes en común, que corresponden a 26 y 30 % del total de los genes de respuesta identificados, respectivamente. Es decir, que GCR1 y GPA1 además de regular algunos genes en común, juegan un papel totalmente independiente entre sí.…”
Section: Mecanismos De Regulación De Las Proteínas G Heterotriméricasunclassified